2021 International Statistical Institute Mahalanobis Award: A Tribute to Heleno Bolfarine. (24th September 2021) - Ruggeri, Fabrizio; Bolfarine, Henrique; Bazán, Jorge Luis; Arellano‐Valle, Reinaldo B.; Lachos Davila, Victor Hugo; de Castro, Mário
Summary: The Government of India sponsors the Mahalanobis International Award, which, managed by the International Statistical Institute, is presented every other year at the International Statistical Institute World Statistics Congress. The Mahalanobis Award recognises an individual for lifetime achievements in statistics in a developing country or region. This article celebrates the 2021 winner, Prof. Heleno Bolfarine, who, unfortunately, passed away a few days before the award ceremony.